Perjalanan Menuju Kebahagiaan: Perspektif Al-Ghazali di Era Disrupsi Digital - Kamal, M Royhan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is titled "Journey to Happiness: Al-Ghazali's Perspective in the Digital Disruption Era," aiming to explore a profound understanding of the concept of happiness according to Al-Ghazali, particularly in the context of challenges faced by Generation Z in the digital disruption era. The research method employed is qualitative, utilizing a literature review approach to detail and analyze relevant works containing Al-Ghazali's views on happiness and to explore the impact of digital disruption on the emotional well-being of this generation. The literature review approach is used to identify key concepts in Al-Ghazali's views on happiness and trace their implementation in addressing the challenges confronted by Generation Z in the digital era. The literature review involves in-depth analysis of Al-Ghazali's works and recent studies discussing the relationship between the concept of happiness, spiritual values, and the influence of digital disruption on psychological well-being. Al-Ghazali teaches that true happiness is achieved when one can recognize and become close to Allah SWT, through self-discovery, understanding Allah, comprehending the world, and recognizing the afterlife. The expected outcome of this research is to provide significant insights into how Al-Ghazali's perspective can serve as a source of inspiration and guidance for Generation Z in navigating their journey towards happiness amid the ever-changing dynamics of the times. Additionally, this study aims to contribute to the literature on understanding happiness and spirituality in the context of the digital era.